2024
DOI: 10.1002/advs.202304349
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Chainmail Shelled Dilute Ni─Cu Alloy for Selective and Robust Aqueous Phase Catalytic Hydrogenation

Haifeng Yuan,
Mei Hong,
Xianzhen Huang
et al.

Abstract: Cost‐effective non‐noble metal‐based catalysts for selective hydrogenation with excellent activity, selectivity, and durability are still the holy grail. Herein, an oxygen‐doped carbon (OC) chainmail encapsulated dilute Cu–Ni alloy is developed by simple pyrolysis of Cu/Ni‐metal–organic framework. The CuNi0.05@OC catalyst displays superior performance for atmospheric pressure transfer hydrogenation of p‐chloronitrobenzene and p‐nitrophenol, and for hydrogenation of furfural, all in water and with exceptional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
0
0
Order By: Relevance
“…Yuan et al reported the first CuNi x @OC of a graphylene shell-diluted Ni-Cu alloy catalyst, demonstrating not only controlled shell thickness and metal-support interactions but also synergistic bimetallic alloy effect. 36 The CuNi 0.05 @OC catalyst exhibited excellent performance in the atmospheric pressure transfer hydrogenation of p-chloronitrobenzene and p-nitrophenol, as well as in the hydrogenation of furfural. Theoretical calculations show that properly tuned lattice strains and Schottky junctions can modulate electron density and promote specific adsorption of active centers, thereby enhancing catalytic activity and selectivity.…”
Section: Alloys and Strain Effectsmentioning
confidence: 98%
“…Yuan et al reported the first CuNi x @OC of a graphylene shell-diluted Ni-Cu alloy catalyst, demonstrating not only controlled shell thickness and metal-support interactions but also synergistic bimetallic alloy effect. 36 The CuNi 0.05 @OC catalyst exhibited excellent performance in the atmospheric pressure transfer hydrogenation of p-chloronitrobenzene and p-nitrophenol, as well as in the hydrogenation of furfural. Theoretical calculations show that properly tuned lattice strains and Schottky junctions can modulate electron density and promote specific adsorption of active centers, thereby enhancing catalytic activity and selectivity.…”
Section: Alloys and Strain Effectsmentioning
confidence: 98%